Kinase signalling adaptation supports dysfunctional mitochondria in disease - Skalka, George L.; Tsakovska, Mina; Murphy, Daniel J. (Frontiers in Molecular Biosciences, 2024)
Mitochondria form a critical control nexus which are essential for maintaining correct tissue homeostasis. An increasing number of studies have identified dysregulation of mitochondria as a driver in cancer. However, which pathways support and promote this adapted mitochondrial function? A key hallmark of cancer is perturbation of kinase signalling pathways. These pathways include mitogen activated protein kinases (MAPK), lipid secondary messenger networks, cyclic-AMP-activated (cAMP)/AMP-activated kinases (AMPK), and Ca2+/calmodulin-dependent protein kinase (CaMK) networks. These signalling pathways have multiple substrates which support initiation and persistence of cancer. Many of these are involved in the regulation of mitochondrial morphology, mitochondrial apoptosis, mitochondrial calcium homeostasis, mitochondrial associated membranes (MAMs), and retrograde ROS signalling. This review will aim to both explore how kinase signalling integrates with these critical mitochondrial pathways and highlight how these systems can be usurped to support the development of disease. In addition, we will identify areas which require further investigation to fully understand the complexities of these regulatory interactions. Overall, this review will emphasize how studying the interaction between kinase signalling and mitochondria improves our understanding of mitochondrial homeostasis and can yield novel therapeutic targets to treat disease.